Grammar Prevention (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
This research deals with the method of grammatical prohibition, especially in the structure and the structural aspect. It has developed the Arab origins and rules that can not be excluded. The research examines the term general prohibition and the similar terms that fall within the grammarians. Prevention is a general concept expressed in more than one term In this research, the research includes what is prohibited in the structure of the news novice news or the news of the acts of initiation, as well as the issues of prevention in the composition of the addition, as well as the study of what prevents the meeting, and what does not dissuade him, and issues of prevention in the structure of the name of the signal and structure of the act and what does not enter it, As well as prevention in the composition of the appeal, and the structure of the conscience of the actor and conscien